(3TQM Ydi GdTeSjIs - (3eLghds
(3ChdgG (B:s
(3GdMeO dhdjI hGdUdGI Ydi fHjg bhdg hQJHJg Ydi ebOeI hKdGK ebGdGJ hNGJeI Cbhd gcPG hLOfG YHGQI GdeJf aj cKjQ ef GdfSN hGdUhGH Cf daXI KdGK ggfG RGFOI hbYJ SghG ef bde GdfGSN (B...s
(3BNQgG (B:s
... (3dhdG GdbQjfI aj GdGTJQGc jJQOO Hjf GdebUhO hHjf eG djS HebUhO hdcf jNJed Gf jMed GddaX Ydi ZjQ GdebUhO ajchf CQOi ef GSJYeGd GdCdaGX GdZQjHI EP dG jage ggfG TjA CUdG (B... (3JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs